BLOCKCHAIN-TECHNOLOGIES: STATE AND PROSPECTS OF DEVELOPMENT IN UKRAINE - KRAVCHENKO, OLENA; SHAPOVAL, OLEKSII; NEBABA, NATALIA; BOTVINOV, ROSTISLAV (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article investigates the origin and development of distributed registry technology - blockchain. It serves as a database and is a reliable form of information storage. The global application of blockchain technology is widespread. Such countries using blockchain as USA, Estonia, Germany, Japan, Great Britain, UAE were analyzed. The technology is used in various industries and spheres of activity: public administration, non-cash payments, financial and production activities, the sphere of various professional services, the sphere of social security, etc. This allows to simplify activities and improve the level of state development. Ukraine is one of the countries that use blockchain technologies and one of those, where these technologies are used at the state level. The most commonly used blockchain in the field of high-tech enterprises (Fintech), at the household level, the blockchain is closely linked to the circulation of cryptocurrencies. Today there are about a hundred companies and projects in the blockchain industry of Ukraine. Among the main projects using this technology are: electronic land auctions, the activity of the State Land Cadaster, the State Register of Real Property Rights and the System of electronic trade in seized property. The main advantages and disadvantages, existing problems, prospects for development, and domestic projects using blockchain technology in Ukraine are identified. Analyzing users’ search queries on the Internet allowed us to conclude the growing interest in these last hours. SWOT analysis was conducted to determine further prospects for the use of the blockchain in Ukraine: the main strengths and weaknesses of the use of the blockchain in various fields are identified, and its potential opportunities and threats are described.